Activation of the mouse DNA polymerase beta gene promoter by adenovirus type 12 E1A proteins. - Yamaguchi, M (1992)
A plasmid carrying the 5'-flanking region (-1852 to +33 with respect to the transcription initiation site) of the mouse DNA polymerase beta gene fused with the chloramphenicol acetyltransferase (CAT) gene was cotransfected into mouse N18TG2 cells with adenovirus type 12 E1 genes-expressing plasmids. Expression of E1A gene products resulted in the elevation of the CAT expression by 3 to 7 folds, but that of E1B gene product was much less effective. RNase protection analysis revealed that the activation by E1A was at the transcription process. Both the 13S E1A and the 12S E1A activated the DNA polymerase beta gene promoter, indicating that the activation domain of E1A is in a common region(s) of 13S and 12S E1A products. The major target sequence of E1A was mapped within the 10 base pair-region (-30 to -20) of the DNA polymerase beta gene promoter, which overlapped with the palindromic sequence known as the ATF(CREB)/E4F-binding consensus. The results suggest that the palindromic sequence is essential for E1A-induced transcriptional activation of the mouse DNA polymerase beta gene.